New Meaningful Effects in Modern Capital Structure Theory - Brusov, Peter; Filatova, Tatiana; Orekhova, Natali; Kulik, Veniamin; Weil, Irwin (Journal of Reviews on Global Economics, 2018)
Paper is devoted to describe the new meaningful effects in capital structure theory, discovered within modern theory of capital cost and capital structure, created by Brusov, Filatova and Orekhova (BFO theory). These qualitatively new effects are present in general version of BFO theory and absent in its perpetuity limit (Modigliani - Miller theory). BFO theory has changed some main existing principles of financial management. Discovered effects modify our understanding of financial management and dictate some unusual managerial decisions.